Diagnostic Accuracy and Interobserver Agreement of Quasistatic Ultrasound Elastography in the Diagnosis of Thyroid Nodules - Cantisani, V.; Lodise, P.; Di Rocco, G.; Grazhdani, H.; Giannotti, D.; Patrizi, G.; Medvedyeva, E.; Olive, M.; Fioravanti, C.; Giacomelli, L.; Chiesa, C.; Redler, A.; Catalano, C.; D’Ambrosio, F.; Ricci, P. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: To assess the best technique and the diagnostic accuracy of Quasistatic Ultrasound Elastography (QUE) in thyroid nodules. Interobserver agreement was also evaluated.Materials and Methods: A preliminary study of 50 patients with 54 thyroid nodules was performed with quantitative software in order to define the best cut-off value of different imaging methods. All patients underwent total thyroidectomy and histopathology findings served as the standard of reference. Thereafter, 154 nodules in 137 consecutive patients were prospectively evaluated by three operators. Findings at fine-needle aspiration cytology and histopathology (N = 60) served as the standard of reference.Results: The most accurate technique was the axial peri-intranodular measurement method which achieved an area under the ROC curve of 0.961 (95 %CI 0.848 – 1.00) and had an optimal cut-off value of 3.00. QUE in the differentiation of thyroid nodules showed for operator 1: sensitivity 90 % (95 %CI 73.5 – 97.9 %), specificity 92.7 % (95 %CI 86.7 – 96.6 %), LR+ 12.40 (6.54 – 23.50), LR- 0.11 (0.04 – 0.32) and accuracy 91.4 % (95 %CI 85.4 – 97.3 %); for operator 2: sensitivity 86.7 % (95 %CI 69.3 – 96.2 %), specificity 87.1 % (95 %CI 79.9 – 92.4 %), LR+ 6.72 (4.16 – 10.80), LR- 0.15 (0.06 – 0.38) and accuracy 86.9 % (95 %CI 80.0 – 93.7 %); for operator 3: sensitivity 80 % (95 %CI 61.4 – 92.3 %), specificity 83.9 % (95 %CI 76.2 – 89.9 %), LR+ 4.96 (3.20 – 7.70), LR- 0.24 (0.12 – 0.49) and accuracy 81.9 % (95 %CI 74.0 – 89.9 %). Interobserver agreement values between operator 1 and operator 2 (k = 0.79) (p < 0.05, 95 %CI 0.684 – 0.904), between operator 1 and operator 3 (k = 0.73, 95 %CI: 0.607 – 0.854) and between operator 2 and operator 3 (k = 0.71, 95 %CI: 0.584 – 0.835) were significant.Conclusion: QUE provides accurate quantitative evaluation of thyroid nodules with low interobserver variability.
Keywords: thyroid nodules; ultrasound elastography; color Doppler ultrasound; thyroid